Anthracyclines Suppress Both NADPH Oxidase- Dependent and -Independent NETosis in Human Neutrophils - Khan, Meraj A. (Cancers (Basel), 2019)
Neutrophil extracellular traps (NETs) are cytotoxic DNA-protein complexes that play positive and negative roles in combating infection, inflammation, organ damage, autoimmunity, sepsis and cancer. However, NETosis regulatory effects of most of the clinically used drugs are not clearly established. Several recent studies highlight the relevance of NETs in promoting both cancer cell death and metastasis. Here, we screened the NETosis regulatory ability of 126 compounds belonging to 39 classes of drugs commonly used for treating cancer, blood cell disorders and other diseases. Our studies show that anthracyclines (e.g., epirubicin, daunorubicin, doxorubicin, and idarubicin) consistently suppress both NADPH oxidase-dependent and -independent types of NETosis in human neutrophils, ex vivo. The intercalating property of anthracycline may be enough to alter the transcription initiation and lead NETosis inhibition. Notably, the inhibitory doses of anthracyclines neither suppress the production of reactive oxygen species that are necessary for antimicrobial functions nor induce apoptotic cell death in neutrophils. Therefore, anthracyclines are a major class of drug that suppresses NETosis. The dexrazoxane, a cardioprotective agent, used for limiting the side effects of anthracyclines, neither affect NETosis nor alter the ability of anthracyclines to suppress NETosis. Hence, at correct doses, anthracyclines together with dexrazoxane could be considered as a therapeutic candidate drug for suppressing unwanted NETosis in NET-related diseases.